COMPARATIVE ANALYSIS OF THE QUALITY AND COST OF ROAD PATCHING USING COLD PAVING HOT MIX ASBUTON (CPHMA) WITH PENETRATION LAYER USING PERTAMINA'S EX ASPHALT - Slamet Budirahardjo; Mohammad Debby Rizani; Galih Widyarini; Muhammad Zidan Fathur Rohman; Aminarti Laela; Mimin Aminah Yusuf (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2026)
Road damage in the form of holes in flexible pavement can reduce the level of road service and endanger road users. Handling road damage requires effective maintenance methods, good pavement quality, and efficient implementation costs. This study aims to compare the quality and cost of road paving work using the Cold Paving Hot Mix Asbuton (CPHMA) method and the Macadam Penetration Layer (Lapen) method on the Bandar-Tulis Road Section, Batang Regency. The research method used is a quantitative method with data collection through field observation, laboratory testing using the Marshall method, and cost analysis based on Work Unit Price Analysis (AHSP). The quality parameters analyzed included Marshall stability values, flow values, and Marshall Quotient (MQ), while cost aspects were analyzed based on the need for labor, materials, and equipment for every 1 m³ of work. The results of the study showed that the CPHMA method had better pavement quality than the Macadam Penetration Layer method. The Marshall Quotient (MQ) value in the CPHMA method ranges from 63,114–126,562 kg/mm, which indicates the blend's ability to resist deformation and traffic loads better. In terms of implementation, the CPHMA method is more practical and efficient because it uses ready-to-use mixtures so that the work time is faster and the use of equipment is less. Based on the cost analysis, the unit price of the CPHMA method is IDR 6,616,846.56/m³, while the Macadam Penetration Layer method is IDR 2,903,370.78/m³. The cost difference between the two methods is Rp3,713,475.78/m³ or around 56.12%, so that the Macadam Penetration Layer method is more economical than the CPHMA method. Thus, the CPHMA method is superior in terms of quality and efficiency of work implementation, while the Macadam Penetration Layer method is superior in terms of cost. The selection of road patching methods needs to consider the condition of road damage, the need for traffic services, and the availability of the road maintenance budget.